2002
DOI: 10.1128/aac.46.10.3168-3174.2002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activity of GSQ1530, a New Heteroaromatic Polycyclic Compound

Abstract: GSQ1530 is a compound derived from a newly identified class of antibiotics referred to as heteroaromatic polycyclic (HARP) antibiotics. The aim of this study was to assess the in vitro antimicrobial activity of GSQ1530. By using an NCCLS broth microdilution assay, the activities of GSQ1530 and other antibiotics were coevaluated against 215 clinical isolates. The MICs at which 90% of isolates are inhibited (MIC 90 s) of GSQ1530 for methicillin-susceptible Staphylococcus aureus and methicillin-resistant S. aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Despite the issues noted above, the current findings showing that MBX-1066 and MBX-1162 are most potent against DNA and RNA synthesis are consistent with the outcomes of studies of another series of DNA binding antibacterial agents (36). The potent inhibition of DNA and RNA synthesis observed in our studies is most likely to be the consequence of the DNA binding activity of these compounds and actually parallels the relative DNA binding affinities of these compounds (see above).…”
Section: As It Was Too Weak) These Values Indi-supporting
confidence: 79%
“…Despite the issues noted above, the current findings showing that MBX-1066 and MBX-1162 are most potent against DNA and RNA synthesis are consistent with the outcomes of studies of another series of DNA binding antibacterial agents (36). The potent inhibition of DNA and RNA synthesis observed in our studies is most likely to be the consequence of the DNA binding activity of these compounds and actually parallels the relative DNA binding affinities of these compounds (see above).…”
Section: As It Was Too Weak) These Values Indi-supporting
confidence: 79%
“…During the last decade, a series of reports on new classes of compounds that bind to DNA and display potent antibacterial activity were published [12][13][14][15][16]. These antibacterial activity.…”
Section: Introductionmentioning
confidence: 98%
“…As a result, they inhibit DNA replication and RNA transcription and consequently kill bacteria. 13 More recently, we described an optimization process in which the influence of the N-and C-terminal units of tetra-heterocyclic compounds on in vitro potency and acute tolerability was investigated. 14 In this study, several new end-terminal substituents were identified; a prototypic structure (1), which has shown in vivo efficacy against a lethal S. aureus infection in the mouse peritonitis model, is shown in Figure 1.…”
mentioning
confidence: 99%